2015
DOI: 10.1016/j.mad.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of pro-longevity genes among mammals

Abstract: Genes which confer a relative longevity advantage may be regulated at the level of transcription or translation. Alternatively, pro-longevity genes may mediate their effects at the level of protein structure-functional relationships that are beneficially optimized in long-lived species. Longevity associated genes (LAGs) may be operationally defined as genes that confer beneficial effects and are relatively more conserved among long-lived species. Global and local protein sequence alignments of over 10,000 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Interestingly, using lentiviral vector based SARS-COV-2 pseudovirus, we found that STAT3 or HSP90 inhibitors treatment blocked the entry of SARS-COV-2 pseudovirus as well, which is consistent with the ndings from other groups showing that the propagation of SARS-COV-2 in host cells is dependent on IL6-STAT3 signaling and HSP90 expression Ulhaq and Soraya, 2020). Together with these observations, our work provides further credence to the pivotal roles of IL6-STAT3-HSP90 signaling axis mediating viral entry, expanding the functional repertoires of IL6 and HSP90 as canonical biomarkers for in ammation, cancer, and aging (Fuhrmann-Stroissnigg et al, 2018;Lindborg et al, 2015;Tanaka et al, 2014;Whitesell and Lindquist, 2005). Furthermore, our data together with recent ndings from other groups suggest that IL6 and HSP90 may serve as risk factors of susceptibility to viral infection Lubkowska et al, 2021;Ulhaq and Soraya, 2020), highlighting the feasibility and rationality of developing targeted therapies towards IL6-STAT3 signaling and HSP90 for viral diseases in the future.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, using lentiviral vector based SARS-COV-2 pseudovirus, we found that STAT3 or HSP90 inhibitors treatment blocked the entry of SARS-COV-2 pseudovirus as well, which is consistent with the ndings from other groups showing that the propagation of SARS-COV-2 in host cells is dependent on IL6-STAT3 signaling and HSP90 expression Ulhaq and Soraya, 2020). Together with these observations, our work provides further credence to the pivotal roles of IL6-STAT3-HSP90 signaling axis mediating viral entry, expanding the functional repertoires of IL6 and HSP90 as canonical biomarkers for in ammation, cancer, and aging (Fuhrmann-Stroissnigg et al, 2018;Lindborg et al, 2015;Tanaka et al, 2014;Whitesell and Lindquist, 2005). Furthermore, our data together with recent ndings from other groups suggest that IL6 and HSP90 may serve as risk factors of susceptibility to viral infection Lubkowska et al, 2021;Ulhaq and Soraya, 2020), highlighting the feasibility and rationality of developing targeted therapies towards IL6-STAT3 signaling and HSP90 for viral diseases in the future.…”
Section: Discussionsupporting
confidence: 91%
“…However, due to species evolution, interspecies studies have to deal with the problem of non-independence of the data due to evolutionary relationships 71 . Therefore, it is important to elucidate whether a specific trait correlates with longevity differences, or alternatively, these differences arise because of the data similarity, by applying statistical phylogenetic comparative methods, such as PGLS 32 , 72 74 , 14 , 23 , 28 , 75 . In the present study, PGLS revealed that pyridoxamine and succinate plasma content changes associated with longevity were not due interspecies relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Genes for breast cancer 1, early onset, and growth hormone (GH) receptor strongly associate with maximum life span across mammalian species. 57,58 The breast cancer 1, early onset, gene occurs with different genotype frequencies in centenarian populations compared with controls. 59 A GH receptor gene exon 3 deletion alters GH sensitivity, and the prevalence of homozygosity for the exon 3 deletion increases with age in longlived individuals.…”
Section: Genetic and Environmental Influencesmentioning
confidence: 99%